A Case of Yellow Fever Vaccine–Associated Viscerotropic Disease in Ecuador - Douce, Richard W. (The American Society of Tropical Medicine and Hygiene, 2010)
We report the first case of viscerotropic syndrome in Ecuador. Because of similarities between yellow fever and viscerotropic syndrome, the incidence of this recently described complication of vaccination with the 17D yellow fever vaccine is not known. There is a large population in South America that is considered at risk for possible reemergence of urban yellow fever. Knowledge of potentially fatal complications of yellow fever vaccine should temper decisions to vaccinate populations where the disease is not endemic.